STRATEGI MENINGKATKAN DAYA SAING PADA UKM RAJUTDEENZZA DI LAMPUNG - Nawawi, Tony; Darryl (Transpublika Publisher, 2022)
The creative economy has an important role in improving the economy and economic growth, people's welfare, opening up new jobs and reducing unemployment. However, the Covid-19 Pandemic has a significant effect on the sustainability of creative product businesses, the majority of which are SMEs and MSMEs. The purpose of this activity is to help SMEs to increase competitiveness in facing the Covid-19 pandemic situation. The priority partner of the activity is knittingdeenzza craftsmen who produce handicraft products, with various types of knitting ranging from tablecloths, pillowcases, bags, knitted shoes, and currently masks made of knitted yarn and the like. This community service program is located in Lampung. The method offered to partners is training/socialization which includes an introduction to competitiveness, competitiveness strategy, and assessment of competitive advantage through the APP model (asset/performance advantage, potential, and process) as well as a competitiveness model for small businesses. The results of these activities have increased the knowledge of partners about competitiveness, as a source of strength of partners in the face of increasingly tough competitive conditions. This is evident from the results of the evaluation after the training, from the partner's answers, it shows that 100% of the answers about the material obtained have increased the partner's knowledge in increasing competitive advantage.